Latest advances in the regulatory genes of adipocyte thermogenesis - Nie, Tao; Lu, Jinli; Zhang, Hua; Mao, Liufeng (Frontiers in Endocrinology, 2023)
An energy imbalance cause obesity: more energy intake or less energy expenditure, or both. Obesity could be the origin of many metabolic disorders, such as type 2 diabetes and cardiovascular disease. UCP1 (uncoupling protein1), which is highly and exclusively expressed in the thermogenic adipocytes, including beige and brown adipocytes, can dissipate proton motive force into heat without producing ATP to increase energy expenditure. It is an attractive strategy to combat obesity and its related metabolic disorders by increasing non-shivering adipocyte thermogenesis.Adipocyte thermogenesis has recently been reported to be regulated by several new genes. This work provided novel and potential targets to activate adipocyte thermogenesis and resist obesity, such as secreted proteins ADISSP and EMC10, enzyme SSU72, etc. In this review, we have summarized the latest research on adipocyte thermogenesis regulation to shed more light on this topic.